1997
DOI: 10.1111/j.1469-8749.1997.tb07407.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial to compare selective posterior rhizotomy plus physiotherapy with physiotherapy alone in children with spastic diplegic cerebral palsy

Abstract: A randomized clinical trial to compare selective posterior rhizotomy plus physiotherapy with physiotherapy alone in children with spastic diplegic cerebral palsy A randomized controlled single-blind trial was performed to compare lumbo-sacral selective posterior rhizotomy (SPR) followed by intensive physiotherapy, with intensive physiotherapy alone in improving motor function in children with spastic diplegic cerebral palsy. Fifteen patients were randomly assigned to each treatment modality. Patients in the SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
109
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(111 citation statements)
references
References 25 publications
1
109
0
1
Order By: Relevance
“…Steinbok et al (1997) have shown increased improvements in the GMFM, spasticity, and range of movement in children having both SDR and intensive physical therapy. However, they did not find increased improvements in physiological cost index, strength, the Peabody Fine Motor Scale (Folio and Fewell 1983), or in the self-care assessment score (Steinbok et al 1997). Increased improvements in GMFM, tone, active range of motion, passive range of motion, and some gait parameters were also found by Wright et al (1998).…”
Section: Synergistic Patterns After Sdrmentioning
confidence: 99%
See 2 more Smart Citations
“…Steinbok et al (1997) have shown increased improvements in the GMFM, spasticity, and range of movement in children having both SDR and intensive physical therapy. However, they did not find increased improvements in physiological cost index, strength, the Peabody Fine Motor Scale (Folio and Fewell 1983), or in the self-care assessment score (Steinbok et al 1997). Increased improvements in GMFM, tone, active range of motion, passive range of motion, and some gait parameters were also found by Wright et al (1998).…”
Section: Synergistic Patterns After Sdrmentioning
confidence: 99%
“…However, it is debated as to whether a reduction in spasticity improves function (Landau 1974, Sahrmann and Norton 1977, Landau and Hunt 1990, McLaughlin et al 1994. In two separate randomized clinical trials, Steinbok et al (1997) and Wright et al (1998) have found significant functional improvements, as measured by the Gross Motor Function Measure (GMFM, Russell et al 1989), in children undergoing SDR and intensive physical therapy compared with children having intensive physical therapy only. However, in a similar study, McLaughlin et al (1998) found no such improvements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall results in this study were characterized as consistent with previously published results of SDR for spastic diplegia in randomized controlled trials. 20,21,34,37 …”
Section: Case Series With Multiple Spasticity Causesmentioning
confidence: 99%
“…It is thus clear that SDR is much more likely to be appropriate in early childhood. Two of the classic studies of the efficacy of SDR 5,6 were limited to children below 7 years old and showed improvement in gross motor function whereas a third study 7 which extended to 18 years showed only marginal improvement. The current study by MacWilliams et al would appear to confirm that SDR is generally inappropriate in later childhood and adolescence when other factors are more important than spasticity.…”
mentioning
confidence: 99%